Validation of a Questionnaire for Patient Awareness and the Need for a Community-Based Outpatient Antimicrobial Stewardship Program (O-ASP): A Pilot Study - Sohyun Park; Min Jeong Geum; Hee Jung Choi; Chung-Jong Kim; Won Gun Kwack; Eun Kyoung Chung; Sandy Jeong Rhie (MDPI AG, 2021)
An outpatient antimicrobial stewardship program (O-ASP) was developed and implemented to promote appropriate antibiotic therapy in outpatient settings. As active patient involvement is a critical component of an effective O-ASP, this study aimed to develop and validate a questionnaire addressing patient awareness for appropriate antibiotic therapy and the need for pharmaceutical care services (PCS) in the O-ASP in Korea. The questionnaire was drafted based on ASPs and PCS guidelines and validated for content and construct validity using the item-content validity index (I-CVI) and Cronbach's alpha, respectively. The estimated I-CVI and Cronbach's alpha were considered excellent or adequate (≥0.8 and 0.70-0.90, respectively) for most of the survey items (17 out of 23 items). The validated questionnaire was utilized in a pilot survey study, including 112 individuals (37% male) with the mean ± SD age of 37 ± 13 years. Among the survey participants, 68% responded that antibiotics had been prescribed appropriately; however, ≥50% showed a lack of knowledge regarding their antibiotic therapy. The participants expressed the need for PCS as part of an O-ASP in the questionnaire (average Likert score ≥3.4/5). In conclusion, our newly validated questionnaire successfully measured patient awareness and knowledge of antimicrobial use and the need for PCS in the O-ASP.